Implementation of Islamic Education Concepts in Improving The Quality of Education: a Systematic Literature Riview (SLR) - Mokhamad Yaurizqika Hadi; Suwarsih Suwarsih; I’ah Satiatun Sani’ah (Qudwah: Journal of Islamic Education, 2025)
This systematic literature review explores the implementation of Islamic education concepts in enhancing the quality of education. The study examines key principles, methods, and challenges associated with integrating Islamic values into contemporary educational practices. Drawing upon diverse sources, such as journal articles, books, and theses, the research highlights approaches like the talaqqi, deliberation, and tarbiyah methods, which emphasize character development, moral education, and academic excellence. Findings reveal that integrating Islamic values with modern educational techniques can significantly improve learning outcomes and student competencies. However, obstacles such as inadequate teacher training, limited resources, and the need for curriculum adjustments persist. The study underscores the importance of innovative management strategies, teacher development programs, and the adoption of competitive curricula to address these challenges. By harmonizing Islamic teachings with evolving educational needs, this research provides actionable insights for educational institutions aiming to foster holistic student development and enhance overall education quality.